ROS mediated malignancy cure performance of morphological, optical, and electrically tuned Sn doped CeO2 nanostructures - Fazal Abbas; Javed Iqbal; Qaisar Maqbool; Tariq Jan; Muhammad Obaid Ullah; Bushra Nawaz; Mudassar Nazar; M. S. Hussain Naqvi; Ishaq Ahmad (AIP Advances, 2017)
To grapple with cancer, implementation of differentially cytotoxic nanomedicines have gained prime attention of the researchers across the globe. Now, ceria (CeO2) at nanoscale has emerged as a cut out therapeutic agent for malignancy treatment. Keeping this in view, we have fabricated SnxCe1-xO2 nanostructures by facile, eco-friendly, and biocompatible hydrothermal method. Structural examinations via XRD and FT-IR spectroscopy have revealed single phase cubic-fluorite morphology while SEM analysis has depicted particle size ranging 30-50nm for pristine and doped nanostructures. UV-Vis spectroscopy investigation explored that Sn doping significantly tuned the band gap (eV) energies of SnxCe1-xO2 nanostructures which set up the base for tremendous cellular reactive oxygen species (ROS) generations involved in cancer cells’ death. To observe cytotoxicity, synthesized nanostructures were found selectively more toxic to neuroblastoma cell lines as compared to HEK-293 healthy cells. This study anticipates that SnxCe1-xO2 nanostructures, in future, might be used as nanomedicine for safer cancer therapy.